A comparison of 48-week treatment efficacy between clevudine and entecavir in treatment-naïve patients with chronic hepatitis B - Shin, Su Rin (Springer-Verlag, 2011)
PURPOSE: Clevudine and entecavir are currently available in Korea as antiviral drugs against chronic hepatitis B (CHB). We aimed to compare the efficacy of clevudine and entecavir therapy. METHODS: Treatment-naïve CHB patients who received 30 mg of clevudine or 0.5 mg of entecavir a day were analyzed. Mean reduction of hepatitis B virus (HBV) DNA levels, complete virological response (cVR, undetectable HBV DNA by real-time PCR), biochemical response (recovery to normal ALT level), and hepatitis B e antigen (HBeAg) seroconversion rate at the 48th week of treatment were assessed. RESULTS: A number of 59 patients in clevudine group and 61 patients in entecavir group were included. Mean HBV DNA reductions from baseline were similar in the clevudine and entecavir groups, −6.4 versus −6.8 log(10) copies/mL in HBeAg-positive (p = 0.417) and −6.9 versus −7.0 log(10) copies/mL in HBeAg-negative patients (p = 0.640). The proportion of patients who achieved cVR was not different between the two groups, 53 versus 55% in HBeAg-positive (p = 1.000) and 100 versus 95% in HBeAg-negative patients (p = 0.452). Biochemical response rates and HBeAg seroconversion rates were also similar in both the groups. Two (3.4%) patients in clevudine group showed virologic breakthrough with rtM204I mutation using direct sequencing analysis. Clinical myopathy occurred in two (3.4%) patients in clevudine group. CONCLUSION: Mean reduction of viral loads was similar between clevudine and entecavir groups during 48 weeks. However, virologic breakthrough and significant myopathy were noted only in clevudine-treated patients. Therefore, more attention should be paid to patients receiving clevudine.